Serum Exosomal Circular RNA Expression Profile and Regulative Role in Proliferative Diabetic Retinopathy - Li, Xinsheng; Wang, Jingfan; Qian, Huiming; Wu, Yan; Zhang, Zhengyu; Hu, Zizhong; Xie, Ping (Frontiers in Genetics, 2021)
Background: Proliferative diabetic retinopathy (PDR), as one of the main microvascular complications of diabetes mellitus, seriously threatens the visual function of working-age populations, yet, the underlying pathogenesis is still poorly understood. This study aimed to identify the distinct exosomal circRNAs expression in PDR-serum and preliminarily explore the potential pro-angiogenic mechanism of specific exosomal circRNA. Methods: We collected serum samples from 10 patients with PDR and 10 patients with age matched senile cataract to detect the exosomal differential expression genes (DEGs) of circRNAs via high-throughput sequencing, followed by validation of qRT-PCR. Next, bioinformatic analysis including competitive endogenous RNA (ceRNA) network, protein-protein interaction network (PPI), and functional enrichment analyses were performed. In addition, the potential function of circFndc3b (hsa_circ_0006156) derived from high-glucose induced endothelial cells were analyzed on human retinal vascular endothelial cells (HRVECs). Results: In total, 26 circRNAs, 106 miRNAs and 2264 mRNA were identified differentially expressed in PDR-serum exosomes compared with cataract-serum exosomes (change fold > 1, and P < 0.05). A circRNA-miRNA-mRNA ceRNA network was established. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that the mRNAs were mainly enriched in PI3K−Akt signaling pathway, MAPK signaling pathway, Wnt signaling pathway, and VEGF signaling pathway. PPI network and module analysis identified 10 hub genes, such as RhoA, Cdc42, RASA1. Finally, circFndc3b and exosomes derived from high-glucose induced endothelial cells was identified with the capability to facilitate angiogenesis in vitro. Conclusion: Aberrant profiling of exosomal circRNAs in PDR-serum was identified. CircFndc3b derived from high-glucose-induced endothelial cells may play an important role in angiogenesis of PDR.